Performance of Sukuk Issuer in Malaysia - Mohd Saad, N.; Mazlan, M.; Mohamad, N. E. A.; Mohd Yatim, M. N. (Universiti Sains Islam Malaysia, 2024)
The purpose of this study is twofold; (i) to determine the performance of company that issues sukuk based on sukuk principles and (ii) to analyze an association between companies profitability ratios; (i) Operating profit margin (OPM), (ii) Return on Assets (ROA) and (iii) Return on Equity (ROE) with sukuk principles and size of issuance. The study used a secondary data for 30 companies which are gathered from securities commission websites for sukuk principles and size of issuance and Bloomberg for the profitability ratios cover period of 2003 until 2007. The preliminary result shown that, most of the companies issue Murabahah sukuk principle compared with other sukuk principle as their investment based on ranking and there is a significant relationship between OPM and all independent variables but not for other variables.